Covalent Whey Protein–Rosmarinic Acid Interactions: A Comparison of Alkaline and Enzymatic Modifications on Physicochemical, Antioxidative, and Antibacterial Properties. Issue 8 (14th July 2018) - Ali, Mostafa; Keppler, Julia K.; Coenye, Tom; Schwarz, Karin
Abstract: The covalent interactions between whey protein isolate (WPI) and rosmarinic acid (RosA) at two different conditions, alkaline (pH 9) and enzymatic (in the presence of tyrosinase, PPO), at room temperature with free atmospheric air were studied. The conjugates formed between WPI and RosA were characterized in terms of their physicochemical and functional properties. The changes in protein structure were analyzed by intrinsic fluorescence and binding of 8‐anilino‐1‐naphthalenesulfonic acid. The findings show that the covalent interactions caused a decrease in free amino and thiol groups and tryptophan content at both conditions. The decrease at enzymatic conditions was lower than at alkaline conditions. In addition, modified WPI at alkaline conditions exhibited higher antioxidative capacity compared to the modification at enzymatic conditions. However, WPI modified at enzymatic condition showed mild antimicrobial activity against Staphylococcus aureus LMG 10147 and MU50 compared to WPI modified at alkaline conditions and unmodified WPI (control). The modified WPI can be used as multifunctional ingredient into various food products with an additional health promoting effect of the bound phenolic compounds.